NGO activities for solving actual social issues – COVID-19 pandemic - Murawska, Agnieszka (Research on social problems in (pre-)pandemic reality, 2023)
NGOs as well as the government must adapt to the processes occurring in the modern world causing changes in the nature and structure of social problems. Undoubtedly, the last great challenge to be faced in modern times was (is) the COVID-19 pandemic. It was it that exposed the problems faced by people at risk of social exclusion. People with disabilities and seniors, due to physical or housing limitations, are forced to stay in their homes all the time. During the pandemic, this experience became close to a huge group of people. In addition, the multitude of those who are digitally excluded should be highlighted. The purpose of the article will be to try to answer the research question: Did and how did NGOs adapt their activities to the Covid-19 pandemic situation?  The pretext for consideration will be the report of the Klon-Jawor Association on the condition of NGOs “A year in pandemic 2020/2021”.